Research on the Relationship Between Family Factors and Physical Activity Level of Young Children Based on Social Cognitive Theory - Shukla, Deepa; Jagadish, Ravi (Journal of Educational Research and Policies, 2025)
This study aims to explore the influence of family factors on the physical activity levels of young children from the perspective of Social Cognitive Theory. By measuring the physical activity levels of 229 young children in Guangzhou, Foshan, and Zhaoqing, China, and analyzing the survey results from their parents, this study examines the impacts of parental awareness, parental behavioral support, parental psychological support, and the family physical activity environment on children's physical activity levels. The results indicate that parental awareness (β=0.167, p=0.033), parental behavioral support (β=0.186, p=0.021), parental psychological support (β=0.259, p=0.001), and the family physical activity environment (β=0.371, p<0.001) all significantly positively predict the physical activity levels of young children. The overall explanatory power of the model is 42.9% (adjusted R²=0.408), suggesting that family factors play a crucial role in promoting physical activity among young children. The study recommends that enhancing parental awareness, strengthening parental behavior and psychological support, and improving the family physical activity environment can significantly elevate the physical activity levels of young children. This research provides empirical evidence for developing family - based strategies to promote physical activity in young children.